2014
DOI: 10.1248/bpb.b14-00211
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Preconditioning Ameliorates Renal Ischemia-Reperfusion Injury through Antiinflammatory and Antiapoptotic Actions in Rats

Abstract: Renal ischemia-reperfusion (I/R) injury is a major cause of acute kidney injury via inflammation and cell apoptosis. Volatile anesthetics have been shown to exert organ-protective effects against kidney damage in vivo and in vitro. In the present study, we investigated the effects of isoflurane, a commonly used volatile anesthetic, on renal I/R injury and the underlying mechanisms. Rats subjected to renal I/R displayed higher serum creatinine and blood urea nitrogen levels than sham rats as well as severe hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…The present study found that preconditioning induced by volatile anesthetics with 1.5% isoflurane for 0.5 h significantly reduced the LPS‐induced production of TNF‐ɑ, IL‐8 and IL‐1β in both human THP‐1 monocytes and human primary PBMs. These findings regarding the isoflurane‐induced anti‐inflammatory effects in LPS‐stimulated monocytes are consistent with reports from other laboratories . Today, an increasing number of cancer patients receive surgery and general anesthesia is an unavoidable perioperative care for the surgical cancer population.…”
Section: Discussionsupporting
confidence: 91%
“…The present study found that preconditioning induced by volatile anesthetics with 1.5% isoflurane for 0.5 h significantly reduced the LPS‐induced production of TNF‐ɑ, IL‐8 and IL‐1β in both human THP‐1 monocytes and human primary PBMs. These findings regarding the isoflurane‐induced anti‐inflammatory effects in LPS‐stimulated monocytes are consistent with reports from other laboratories . Today, an increasing number of cancer patients receive surgery and general anesthesia is an unavoidable perioperative care for the surgical cancer population.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to endothelial cell integrity, contradicting findings 49,50 may reflect the tested preparation and dose and duration of isoflurane anesthesia. 52,53 Experiments in a TBI model in rats in which different anesthetic and sedative agents, including propofol and ketamine, were administered early after injury showed that rats treated with isoflurane had the best cognitive recovery and hippocampal neuronal survival. 51 In contrast, lower concentrations, as used here, have been reported to protect heart, kidney, and brain tissue from ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…51 In contrast, lower concentrations, as used here, have been reported to protect heart, kidney, and brain tissue from ischemic injury. 52,53 Experiments in a TBI model in rats in which different anesthetic and sedative agents, including propofol and ketamine, were administered early after injury showed that rats treated with isoflurane had the best cognitive recovery and hippocampal neuronal survival. 54 Consistent with our results in the paraoxon model, isoflurane was reported to decrease BBB leakage in a rat stroke model 55 and subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that isoflurane provides preconditioning renoprotective effects through anti-inflammatory and anti-apoptotic actions in a rat model [32]. Isoflurane may be protecting against renal tubular necrosis and inflammation by inducing renal tubular CD73 and adenosine generation, which is dependent on transforming growth factor-beta 1 [33].…”
Section: General Anesthesiamentioning
confidence: 99%